The Meaning of Environmental Care in Strengthening Pancasila Student Profile at SMPN 1 Slawi - Afina, Amelia Nur; Masrukhi, Masrukhi; Sodiq, Ibnu (Journal of Educational Social Studies, 2024)
This research was motivated by the low awareness and implementation of environmentally conscious practices in Tegal Regency, where 18.2 tons of waste are generated daily. This issue is further compounded by the prevalence of littering and a general lack of awareness and understanding of effective waste management practices. This study aims to explore the significance of environmental stewardship among students and its internalization through the Pancasila Student Profile Strengthening Project at SMP Negeri 1 Slawi. The research employed a qualitative case study approach that included observation, in-depth interviews, focus group discussions, and documentation. The findings indicate that despite receiving the Adiwiyata award, implementing environmentally friendly practices at SMP Negeri 1 Slawi remains inadequate. The observation of students littering and the lack of responsibility exhibited in sorting waste suggest that further improvements can be made. The Pancasila Student Profile Strengthening Project successfully optimized students' awareness and behaviour in maintaining cleanliness and waste management. This study suggests enhancing collaboration between schools, families, and communities, as well as government support through policies, infrastructure, and law enforcement to strengthen environmental care programs.